Managers Reports of Automated Coding System Adoption and Effects on Data Quality - Lorence, D. P.; Jameson, R. (Methods of Information in Medicine, 2003)
Objective: Assessment of the adoption of automated classification (encoder) systems in healthcare settings and related effects on perceived data quality.Methods: Survey of all U.S. accredited medical records managers, summarizing their reports of automated encoding systems and data quality change following adoption of systems.Results: Significant improvement in data was seen from adoption of automated encoding systems, though variation existed across regions and key demographic variables.Conclusion: At a national level, there is a need to minimize data quality variation and ensure some degree of nationwide uniformity in the performance of coding systems. If healthcare providers are expected to trust coded data for comparative purposes, there will be a like need for more uniform and standardized system-based performance benchmarks.
Keywords: MeSH terms; evidence-based; quality; classification; data systems